2016
DOI: 10.1016/j.jcis.2016.07.078
|View full text |Cite
|
Sign up to set email alerts
|

Influence of carbon nanotubes and graphene nanosheets on photothermal effect of hydroxyapatite

Abstract: Herein we present a successful strategy for efficient enhancement of photothermal efficiency of hydroxyapatite (HAP) by its conjugation with carbon nanotubes (CNTs) and graphene nanosheets (GR). Owing to excellent biocompatibility with human body and its non-toxicity, implementation of HAP based nanomaterials in photothermal therapy (PTT) provides non-replaceable benefits over currently using PTE agents. Therefore, in this report, it has been experimentally exploited that the photothermal effect (PTE) of HAP h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 81 publications
1
33
0
2
Order By: Relevance
“…The apoptosis rate of group with CNPs was a bit higher than that of groups with CNs (P < 0.05). The results indicated that the CNPs had the excellent photothermal therapeutic effect in vitro , similar to other similar materials33233.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…The apoptosis rate of group with CNPs was a bit higher than that of groups with CNs (P < 0.05). The results indicated that the CNPs had the excellent photothermal therapeutic effect in vitro , similar to other similar materials33233.…”
Section: Resultssupporting
confidence: 54%
“…Moreover, the CNPs have photothermal-conversion effect after exposure to laser. Photothermal therapy is highly effective in oncotherapy43233. In this study, we have shown that CNPs has the therapeutic effect on the tumor, as demonstrated both in vitro and in vivo .…”
mentioning
confidence: 68%
“…In a very recently study, Neelgund et al (Neelgund and Oki, 2016 ) found that CNT could improve the photothermal efficiency (PTE) of HAP, and HAP could also overcome the poor dispersion of CNT. In this work, we proposed the combination of HAP with CNT for fluoride removal from aqueous media.…”
Section: Introductionmentioning
confidence: 99%
“…The spectrum of CNTs‐PLA‐Pd (Figure d) could not demonstrate any individual band corresponding to both CNTs‐PLA and Pd nanoparticles, instead, these bands have merged and appeared as a single band at 274 nm. Moreover, these samples have showed a strong absorption in NIR region between 950–1080 nm, which could be originated by the electronic transitions between the first or second van Hove singularities of the CNTs . The absorption of CNTs‐COOH in NIR region is significantly improved by grafting with PLA and further enhanced by deposition of Pd nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…The total rise in temperature of 43.5, 42.0 and 40.7 °C was recorded at 1, 0.5 and 0.25 mg/mL of concentration, respectively for CNTs‐PLA‐Pd . For further quantification of PTE of CNTs‐PLA‐Pd, its photothermal conversion efficiency (η) was calculated by the help of Roper's method using following equation trueη=hS()Tmax-Tsurr-QdisI(1-10-A980) …”
Section: Resultsmentioning
confidence: 99%